Surveying heterocycles as amide bioisosteres within a series of mGlu7 NAMs: Discovery of VU6019278. Issue 10 (15th May 2019) - Reed, Carson W.; Washecheck, Jordan P.; Quitlag, Marc C.; Jenkins, Matthew T.; Rodriguez, Alice L.; Engers, Darren W.; Blobaum, Anna L.; Conn, P. Jeffrey; Niswender, Colleen M.; Lindsley, Craig W.
Graphical abstract: Highlights: Novel series of selective and CNS penetrant mGlu7 NAMs. Identified a 1, 3, 4-oxadiazole as biosiostere for a labile amide linker. Iterative libraries quickly optimized this novel tricyclic series. Abstract: This letter describes a diversity-oriented library approach to rapidly assess diverse heterocycles as bioisosteric replacements for a metabolically labile amide moiety within a series of mGlu7 negative allosteric modulators (NAMs). SAR rapidly honed in on either a 1, 2, 4- or 1, 3, 4-oxadizaole ring system as an effective bioisostere for the amide. Further optimization of the southern region of the mGlu7 NAM chemotype led to the discovery of VU6019278, a potent mGlu7 NAM (IC50 = 501 nM, 6.3% L-AP4 Min) with favorable plasma protein binding (rat fu = 0.10), low predicted hepatic clearance (rat CLhep = 27.7 mL/min/kg) and high CNS penetration (rat Kp = 4.9, Kp, uu = 0.65).